Arbuscular mycorrhiza improve apple rootstock growth in soil conducive to specific apple replant disease - Ridgway, H.J.; Kandula, J.; Stewart, A. (New Zealand Plant Protection, 2008)
Specific apple replant disease (SARD) impairs the growth and establishment of trees in replanted apple orchards Apple roots are normally colonised by arbuscular mycorrhizal fungi (AMF) which may have beneficial effects on plant growth Four AMF inoculation treatments (three species of AMF Glomus mosseae Acaulospora laevis and Scutellospora calospora and an uninoculated control) were applied to M26 apple rootstock seedlings in SARD and nonSARD soil Of the fungi inoculated S calospora had the greatest beneficial effect in improving shoot and root dry weight and shoot length in SARD soil More disease symptoms occurred on main and feeder roots in SARD soil and none of the inoculated AMF fungi reduced these Both A laevis and S calospora significantly increased shoot length and gave a higher percentage of AMFcolonised roots in nonSARD soil These results showed that AMF improve tolerance of apple to SARD and indicate that the beneficial effect is species specific Characterisation of endogenous mycorrhizae in the soil identified S pellucida This is a new species record for New Zealand and provides the opportunity to determine whether the beneficial effect is specific to the genus Scutellospora